Analisis Puisi “Puisi Untuk Ibu” Karya H. Muhamad Ichsan Dengan Menggunakan Pendekatan Struktural - Tanti Tanti; Dinda Amanda (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
In literary works, for example, literary works in the form of poetry, there must be a form of appreciation and study of literary works that have been created. This study discusses the study of poetry in poetry literature entitled "Poetry for Mother" by H. Muhammad Ichsan. Poetry is one of the literary genres written by poets to express their thoughts and feelings through words that have their own meaning. This poetry study aims to find out the structure contained in the poem entitled "Poems for Mother". The benefit of studying this poem is that it is useful for readers to know the physical and mental structure of the poem entitled "Poems for Mother" by H. Muhammad Ichsan. The method used in this study is the qualitative descriptive method. The approach used by this study is a structural approach, namely physical and mental structures. The data collection technique used in this study is a documentation study. The results of the study obtained are the physical and mental structures contained in the poem entitled "Poems for Mother" by H. Muhammad Ichsan. The physical structure is in the form of poetry, diction, concrete words, language style and imagery, while the inner structure is in the form of themes, tones, atmospheres and messages.